Environmental sustainability, the forgotten aspect that makes nursing invisible - Keydis Sulay Ruidiaz Gómez; Ana Sofía Periñan Martínez; María Alejandra Castilla Laurens (Universidad de Santander, 2023)
Scientific publications in research journals have adeptly investigated into topics of considerable interest, rendering nursing care more intricate in the face of increasingly thorough investigations into numerous phenomena. This ongoing exploration contributes significantly to the body of knowledge disseminated within the scientific community. Nevertheless, the advent of the global era has presented nursing with novel challenges that persist from the dawn of history parallel to a lingering shadow obscuring the true essence of the profession. An example is environmental nursing, often overlooked from the lens of social sustainability-a neglect that researchers, as minority groups in a relentless struggle, have sidelined. These challenges align with the dynamic demands imposed by society and the mandates of state and/or governmental parliaments.